Work-Life Balance and Work Flexibility as Predictors of Employee Performance: The Mediating Role of Organizational Commitment in Start-Up Employees in South Jakarta - Azzahra Khaerunnisa; Nuraeni Nuraeni (Dinasti Publisher, 2025)
This study focuses on the effect of Work-life Balance and Work Flexibility on Employee Performance through Organizational Commitment. with a case study of Start-Up employees in South Jakarta. This study lies in skilled human resources, quality, and human resource management, which will encourage the company's success in achieving its goals which are expected to increase organizational commitment and improve employee performance. The data collection method used in this research is a questionnaire with quantitative research involving start-up employees in South Jakarta, with a sample of 170 respondents selected using the non-probability sampling method with the Malhotra formula. The data was analyzed using the SmartPLS method. The results of this study indicate that Work-Life Balance has a significant positive effect on Employee Performance, Flexibility has a significant positive effect on Employee Performance, Work-Life Balance has a significant positive validity on Organizational Commitment, Work Flexibility has a significant positive validity on Organizational Commitment, Organizational Commitment has a significant positive validity on Employee Performance, Organizational Commitment has a mediating effect on the relationship between Work-Life Balance and Employee Performance, Organizational Commitment has a mediating effect on the relationship between Work Flexibility and Employee Performance.